2021
DOI: 10.1001/jamanetworkopen.2021.39351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mass Azithromycin Distributions on Childhood Growth in Niger

Abstract: IMPORTANCEMass azithromycin distributions may decrease childhood mortality, although the causal pathway is unclear. The potential for antibiotics to function as growth promoters may explain some of the mortality benefit. OBJECTIVE To investigate whether biannual mass azithromycin distributions are associated with increased childhood growth. DESIGN, SETTING, AND PARTICIPANTS This cluster-randomized trial was performed from December 2014 until March 2020 among 30 rural communities in Boboye and Loga departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…We will build on this work and investigate in a subset of villages, the effect of azithromycin on malaria parasitemia, inflammation, and other markers of infection, immunity, and vaccine response. Besides the infection reduction pathway, growth promotion is considered another plausible mechanism that could explain some of the mortality benefit [ 27 ]. Undernutrition is an underlying factor contributing in almost half of all child deaths [ 1 ], and in low- and middle-income settings, antibiotic treatment of children might improve their linear growth [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We will build on this work and investigate in a subset of villages, the effect of azithromycin on malaria parasitemia, inflammation, and other markers of infection, immunity, and vaccine response. Besides the infection reduction pathway, growth promotion is considered another plausible mechanism that could explain some of the mortality benefit [ 27 ]. Undernutrition is an underlying factor contributing in almost half of all child deaths [ 1 ], and in low- and middle-income settings, antibiotic treatment of children might improve their linear growth [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A random sample of children from each community was monitored annually for a 2-year period for numerous health outcomes. The primary outcomes of the sister trial included malaria, anthropometry, and macrolide resistance and are reported elsewhere . Clinical trachoma was a prespecified secondary outcome, defined according to the WHO’s simplified grading system as the presence of trachomatous inflammation–follicular (TF) or trachomatous inflammation–intense (TI) .…”
Section: Methodsmentioning
confidence: 99%
“…The present study assessed prespecified trachoma outcomes of the sister trial included malaria, anthropometry, and macrolide resistance and are reported elsewhere. [17][18][19] Clinical trachoma was a prespecified secondary outcome, defined according to the WHO's simplified grading system as the presence of trachomatous inflammation-follicular (TF) or trachomatous inflammation-intense (TI). 20 This study followed the Consolidated Standards of Reporting Trials (CONSORT) reporting guideline.…”
Section: General Study Designmentioning
confidence: 99%
“…A parallel trial was conducted in 30 communities at the Niger site to monitor additional outcomes separate from the mortality trial (MORDOR morbidity trial). 10 Eligibility, randomisation and census data collection were the same in both trials, as described above. In addition, repeated random samples of 40 children aged 1–59 months were selected at baseline, 6 months, 12 months and 24 months for additional monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…A parallel trial was conducted in 30 communities at the Niger site to monitor additional outcomes separate from the mortality trial (MORDOR morbidity trial) 10. Eligibility, randomisation and census data collection were the same in both trials, as described above.…”
Section: Methodsmentioning
confidence: 99%